2012
DOI: 10.3109/10253890.2012.719052
|View full text |Cite
|
Sign up to set email alerts
|

Chronic stress-induced oxidative damage and hyperlipidemia are accompanied by atherosclerotic development in rats

Abstract: Although stress-induced hyperlipidemia and increased oxidative stress have been reported and implicated in etiology of atherosclerosis, experimental evidence for stress-induced atherosclerotic development concomitant with these alterations is lacking. In this study, exposure of adult male albino Wistar rats (Rattus norvegicus) to restraint for 1 h and after a gap of 4 h to forced swimming for 15 min every day for 2, 4, or 24 weeks resulted in a duration of exposure-dependent hyperlipidemia as shown by signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(46 citation statements)
references
References 46 publications
1
38
0
1
Order By: Relevance
“…In addition, Feng et al demonstrated that forced swim stress elevates cholesterol content in the brain (Feng et al, 2015). Another study using 1 h of restraint in association with forced swim found significant increases in blood cholesterol with stress in rats (Devaki et al, 2013). Herein we show that 15 min a day of psychological stress for 14 days is sufficient to affect circulating cholesterol levels in an obesogenic environment.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Feng et al demonstrated that forced swim stress elevates cholesterol content in the brain (Feng et al, 2015). Another study using 1 h of restraint in association with forced swim found significant increases in blood cholesterol with stress in rats (Devaki et al, 2013). Herein we show that 15 min a day of psychological stress for 14 days is sufficient to affect circulating cholesterol levels in an obesogenic environment.…”
Section: Discussionmentioning
confidence: 99%
“…adrenaline, noradrenaline) as they were not available in SKIPOGH. Moreover, we decided to include an oxidative stress axis as chronic oxidative stress has also been linked to generalized physiological dysregulation (Devaki et al, 2013;Nicod et al, 2014). Further, we separated the lipids from the metabolism axes contrary to previous studies.…”
Section: Allostatic Loadmentioning
confidence: 99%
“…However, some have questioned the relevance of this behavior (floating), since it may be an acquired lifesaving behavior for preserving energy (292,362). Atherosclerosis-promoting effects of forced swimming haves been shown in a stress protocol consisting of restrain and forced swimming in rats fed a normal diet (73). This chronic stress model enhanced different aspects of atherosclerosis including increases in cholesterol and triglycerides blood levels, decreased HDL, increased oxidative stress, reduction of vascular elastic fibers, and boosted foam cell formation.…”
Section: Animal Models Of Physical Stressmentioning
confidence: 99%